2012
DOI: 10.1038/ismej.2012.21
|View full text |Cite
|
Sign up to set email alerts
|

Distinct and diverse anaerobic bacterial communities in boreal lakes dominated by candidate division OD1

Abstract: Lakes have a central role in the carbon cycle of the boreal landscape. These systems typically stratify in summer and their hypolimnetic microbial communities influence burial of biogenic organic matter in sediments. The composition of bacterial communities in these suboxic habitats was studied by pyrosequencing of 16S rRNA amplicons from five lakes with variable dissolved organic carbon (DOC) concentrations. Bacterioplankton communities in the hypolimnetic waters were clearly different from the surface layer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
130
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(151 citation statements)
references
References 68 publications
19
130
2
Order By: Relevance
“…These bacteria are usually regarded as being part of the rare biosphere because of their low relative abundance [5,33,56,61]. A recent study, however, revealed that several members of OD1 were abundant and consistently present in the suboxic hypolimnion of boreal lakes [43]. Our study adds to this list with another scenario: a rare taxon of the candidate division OD1 that is sometimes abundant in the cytoplasm of the ciliated protist Paramecium bursaria.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…These bacteria are usually regarded as being part of the rare biosphere because of their low relative abundance [5,33,56,61]. A recent study, however, revealed that several members of OD1 were abundant and consistently present in the suboxic hypolimnion of boreal lakes [43]. Our study adds to this list with another scenario: a rare taxon of the candidate division OD1 that is sometimes abundant in the cytoplasm of the ciliated protist Paramecium bursaria.…”
Section: Discussionmentioning
confidence: 66%
“…Ecological and metagenomic data may provide further indications as to the role of the OD1 bacterium in the three-partner consortium. It has been reported that members of the OD1 group are most likely to be anaerobes and may engage in sulfur cycling in various habitats [3,11,16], as well as anaerobic methane oxidation in boreal lakes [43]. A recent metagenomic survey of an acetate-amended aquifer showed that members of OD1 play roles in sulfur cycling and fermentation of refractory sedimentary carbon to produce acetate, ethanol, lactate, and hydrogen [70].…”
Section: Discussionmentioning
confidence: 99%
“…This finding was later supported by complete genomes for members of SR1, OD1 and WWE3 recovered from acetate-stimulated sediments from this same site (Kantor et al, 2013). These phyla have been identified from non-carbon amended sediments from the same metal-contaminated aquifer and pristine environments (Briée et al, 2007;Peura et al, 2012).…”
Section: Introductionmentioning
confidence: 54%
“…Two ponds, KWK-1 and -12, were typical freshwaters, with low conductivity and warmer surface temperatures in summer, and contained a higher proportion of Betaproteobacteria, typical of freshwater (Hiorns et al 1997, Van der Gucht et al 2005, including a boreal humic lake (Peura et al 2012). Bacteroidetes, related to Sediminibacterium, which is reported to produce H 2 S (Qu & Yuan 2008), were also found in both of these ponds and in KWK-6.…”
Section: Surface Bacterial Assemblagesmentioning
confidence: 93%